The representation of the medical doctor in the non-medical sources of the palaiologan period - Tabur, İpek. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2008., 2008)
This thesis aims to examine the physicians of the Palaiologan period and their place in late Byzantine society as reflected in the non-medical literary sources of the period, which include histories, chronicles, letters, hagiographical literature, poems, satires, patriarchal court registers, monastic acts, and typika. The awareness exhibited by the non-medical sources of medical practice and its practitioners indicates that physicians during the Palaiologan period (1261-1453) were too influential to be neglected by the sources of the time. An examination of the sources, besides offering interesting information on the personalities of the physicians, also helps one to trace the developments that took place in medicine, its practice and education in the Palaiologan period. This thesis is comprised of four chapters. Following the introductory Chapter One, Chapter Two focuses on the Palaiologan hospitals, since in the Byzantine Empire medical science, its practice and education were largely organized around the hospital complexes. In Chapter Three the physicians as they appear in the sources are introduced within separate subsections arranged according to the centuries in which they practiced medicine, followed by an interpretation of the data compiled here. The final chapter, Chapter Four, is reserved for the concluding remarks.
Keywords: Byzantine Empire -- History -- Palaeologi dynasty, 1259-1448.; Physicians -- History.